Building Customer Loyalty Through the 7P Service Marketing Mix: The Mediating Role of Reputation in the Context of PT “SUN” Accounting Firm - Yulia Andriani; Metta Padmalia (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study examines the effect of the 7P marketing mix on customer loyalty at PT Synergy Ultima Nobilus (SUN), with corporate reputation serving as a mediating variable. Using a purposive sampling method, data from 95 respondents were analyzed using the PLS-SEM approach. The results of the analysis indicate that the product (service quality), people (human resources), and tangible evidence elements have a positive and significant effect on corporate reputation. Meanwhile, the price, place, promotion, and process elements do not have a significant effect. Furthermore, corporate reputation was found to have a significant effect on customer loyalty, acting as a partial mediator for the product element and a full mediator for the people and tangible evidence elements.